Time remaining:
Simplify. Identify any x-values for which the expression is undefined.

Algebra
Tutor: None Selected Time limit: 1 Day

x^2-2x-3 / x^2+5x+4

Nov 13th, 2014

(x2-2x-3) /( x2+5x+4)= ((x2-3x+x-3)/ ( x2+4x+x+4)

=[x(x-3)+1(x-3)][x(x+4)+1(x+4)]

=[(x-3)(x+1)]/[(x+4)(x+1)]

The expression is undefined for x=-4 and x=-1

If x not equal to -1 then this becomes (x-3)/(x+4)

This is not valid for x= -4



Nov 13th, 2014

Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.
Click to visit
The Notebank
...
Nov 13th, 2014
...
Nov 13th, 2014
Feb 23rd, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer